Developing Strategies for a Seafood-Based Food Stall Using BMC, SWOT, and AHP Approaches - Rofiqoh Nur Rohmah; Maya Revanola Zainida; Gilang Titah Ramadhan (LPPM Telkom University Surabaya, 2025)
Indonesia holds vast marine potential that remains underutilized, particularly in downstream processing within the micro-scale seafood culinary sector. Seafood-based eateries play a critical role in strengthening local economies and supporting the implementation of the blue economy. However, these businesses still face structural challenges, including limited technological adoption, market access barriers, and unstructured business models. This study aims to formulate and prioritize development strategies for seafood-based microenterprises using a combination of the Business Model Canvas (BMC), SWOT analysis, and the Analytic Hierarchy Process (AHP). A mixed-method approach was employed, incorporating interviews, field observations, and expert surveys. The BMC analysis showed that the business had some major strengths, such as a wide range of menu items, the use of fresh ingredients every day, and a high level of customer loyalty. At the same time, weaknesses included limited visibility in locations, limited digital integration, and conventional operational systems. The SWOT analysis generated five strategic alternatives, which were evaluated using AHP based on five criteria: sustainability, technical feasibility, local economic impact, business competitiveness, and implementation cost. The findings indicate that the internal strengthening strategy—comprising staff training, business expansion, and supplier selection—is the most feasible and prioritized approach. However, this strategy does not fully embody the core principles of the blue economy. Therefore, policy interventions and cross-sector collaboration are essential to integrate micro-scale seafood businesses into a sustainable and inclusive maritime ecosystem.